The Role Of Nurses In Preventing Gangreneous Wounds In Diabetes Mellitus Patients At H. Sahudin Kutacane Hospital - Sri Mala Hayati; Ade Kartika (Jurnal EduHealth, 2023)
Diabetes mellitus is one of the most common diseases in Indonesia. Diabetes mellitus is a disease characterized by chronically elevated blood sugar levels that can affect many people from all levels of society. One of the risk factors for diabetes mellitus is the level of knowledge, the role of nurses and support from health workers in gangrene prevention behavior. The aim of this research is to determine the role of nurses in preventing gangrene wounds in diabetes mellitus sufferers at H.Sahuddin Kutacane Regional Hospital. This research method uses a quantitative type of correlational research with a cross-sectional research design. The sample was 29 nurse at the H. Sahudin Kutacane Regional Hospital, using a simple random sampling technique. Data were collected using a questionnaire on the level of knowledge, the role of nurses and support from health workers in behavior to prevent gangrene wounds. The variables studied were the level of knowledge, the role of nurses and support from health workers as the dependent variable and the independent variable was behavior to prevent gangrene wounds. The data analysis used was the spearmen rho correlation statistical test. The results of the study showed that almost half of the diabetes mellitus patients at H. Sahudin Kutacane Hospital had a level of knowledge (25%) with behavior to prevent gangrene wounds, while the role of nurses or support from health workers with behavior to prevent gangrene wounds was (21%). The results of statistical test analysis using Spearman Correlation show that the value Ho = 0.000 is known to be p < (0.05). Which means that there is a role for nurses in preventing gangrene wounds in diabetes mellitus sufferers. As for the researchers' suggestions, the H. Sahuddin Regional Hospital should be able to increase the provision of information and provide leaflets/brochures to diabetes mellitus patients about preventing gangrene wounds as one of the successes of therapy in diabetes mellitus patients.